ETHICAL VIEWS OF IMMANUEL KANT (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
Immanuel Kant was a German philosopher who had a great influence on modern philosophy and ethics. His ethical views are based mainly on deontological ethics, which emphasizes that the correctness of actions in making moral decisions is based on their specific rules and obligations, not on their results. Kant's ethics includes important concepts such as human freedom, responsibility and moral obligations.